Zmiany w podatku od towarów i usług w latach 2017–2018 - Kopyściańska, Katarzyna; Skwierczyńska, Ewelina (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The subject of consideration is the analysis of selected changes in the tax on goods and services, which is commonly referred to so called "sealing the system". It is a reaction to these behaviors of legal and economic turnover, which can be classified as abuse of the tax system. Increase of goods and services tax collection effectiveness required enhanced analytical activities of the tax office. It also increase the tax office ability to model, forecast and predict the phenomena of economic turnover, whose negative effects affect the efficiency of the tax system.
Keywords: tax on goods and services; split payment mechanism; SIT system; VAT account; Sealing; tax gap; centralization; VAT; precoefficient; e-declarations; exchange of information - SCAC; chain transactions